How Is The Implementation Of Mandatory Indonesian National Standards (SNI) For Children’s Toys Products According To Law No. 3 Of 2014 Concerning Industry - Adellya, Novrisa; Erniwati, Erniwati; Agustina, Sakinah (Fakultas Hukum Dehasen, 2025)
This study discusses the implementation of the mandatory Indonesian National Standard (SNI) for children’s toy products based on the provisions of Law Number 3 of 2014 concerning Industry. The aim of this research is to analyze how the obligation to apply SNI is implemented by business actors and supervised by the government in ensuring the safety of children's toys circulating in society. The research method used is a normative juridical approach utilizing secondary data derived from legislation, legal textbooks, and scientific journals. The results of the study indicate that the obligation to apply SNI to children's toy products is a form of legal protection for child consumers, but its implementation in the field still faces various obstacles ranging from lack of supervision to the low awareness of business actors.